2017
DOI: 10.1016/j.ejmp.2017.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the effect of 4 MeV electron beam using gold nanoparticles in breast cancer cells

Abstract: Gold nanoparticles (GNPs) have been applied as radiosensitizer in radiotherapy. Limited reports have shown that GNPs may be effective as a dose enhancer agent for electron radiation therapy. Some Monte Carlo Simulation studies have shown that selecting suitable size of GNPs and electron energies are critical for effective dose enhancement. The aim of this study was to assess possible radiosensitization effect of GNPs on cancer cell treated with 4MeV electron beams. Approximately 10nm GNPs were synthesized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Furthermore, we examined the bystander effects of irradiated MCF-7 cells on the different cell lines, which are known play pivotal roles in cancer treatment. Consistent with previous studies (20,21), we found that the cell viability and apoptosis rate of irradiated MCF-7 cells were dose-dependently decreased and increased respectively (Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we examined the bystander effects of irradiated MCF-7 cells on the different cell lines, which are known play pivotal roles in cancer treatment. Consistent with previous studies (20,21), we found that the cell viability and apoptosis rate of irradiated MCF-7 cells were dose-dependently decreased and increased respectively (Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the potential exists for damage to surface ligands or other organic components of the system. Indeed, prior radiation chemistry studies have shown GNPs have a significant “dose enhancement” effect in water. The sensitization effect of gold, reported to increase the effective dose by nearly 100 times under X-ray radiation, , is chiefly caused by the irradiation-triggered release of secondary electrons and X-rays from GNPs, which directly radiolyze the surrounding solution, causing an effective local dose increase. Thus, in water, any organic molecule is expected to readily undergo indirect beam-induced damage during LCTEM, , and this chemical damage should be enhanced by GNPs or mitigated by a scavenging alcohol cosolvent.…”
mentioning
confidence: 99%
“…In vivo and in vitro works by Chang et al showed GNPs radiosensitizing effect at high energy electron beams (50). To test our hypothesis that GNPs induce radiosensitization effect in the 4 MeV electron radiation beam condition, we made preliminary studies to measure the effect of 10 nm GNPs at different concentrations (51). Our previous data showed that this sensitizing effect depends on GNP's concentrations and the radiation dose.…”
Section: Discussionmentioning
confidence: 98%